2021
DOI: 10.1186/s43045-021-00103-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health symptoms among the nurses of Bangladesh during the COVID-19 pandemic

Abstract: Background The coronavirus disease-19 (COVID-19) pandemic has wreaked havoc on healthcare staff and caused serious psychological distress. We aimed to determine the effects of the COVID-19 pandemic on the mental health of Bangladeshi nurses, as well as the relationship between occupational factors and mental health symptoms. We conducted a cross-sectional study among registered nurses in Bangladesh. We used the Depression, Anxiety and Stress Scale-21 (DASS-21) and the Impact of Event Scale-Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 28 publications
4
41
0
2
Order By: Relevance
“…After more than a year since the emergence of SARS-CoV-2, it has now spread to nearly 200 countries around the globe with a staggering number of 120 million confirmed cases and 2.6 million deaths [ 1 , 2 ]. It has brought the world to its knees, imposing lockdowns, closure of academic institutions, inciting adverse psychological impacts, adopting the e-learning education system and work from home policy [ 3 5 ]. The world is relentlessly searching for new strategies to cope with the ‘new normal’ and resume daily work and business.…”
Section: Introductionmentioning
confidence: 99%
“…After more than a year since the emergence of SARS-CoV-2, it has now spread to nearly 200 countries around the globe with a staggering number of 120 million confirmed cases and 2.6 million deaths [ 1 , 2 ]. It has brought the world to its knees, imposing lockdowns, closure of academic institutions, inciting adverse psychological impacts, adopting the e-learning education system and work from home policy [ 3 5 ]. The world is relentlessly searching for new strategies to cope with the ‘new normal’ and resume daily work and business.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gender also affected stress where women were twice as susceptible to stress as men (Wilson et al, 2020). Nurses with lower level of educational were less psychological impact from the COVID-19 pandemic, had lower DASS scores, and lower mental distress than the higher education (Chowdhury et al, 2021). Nurses with longer years of service have more clinical experience, making it easier to adapt to patients care, especially during a pandemic like this.…”
Section: Resultsmentioning
confidence: 99%
“…This working nature of the nurses may propel more fear. The Bangladeshi nurses were gone through mental health-related symptoms during the first web of the COVID-19 pandemic [43]. Similarly, Tayyib et al reported a high level of fear and stress among the nurses during the COVID-19 context [44].…”
Section: Discussionmentioning
confidence: 99%